Worker Social capital of working women "putting-out system" to rise from Covid-19 pandemic - Siti Sofiyah; Emy Susanti; Sutinah (Jurnal Studi Komunikasi, 2023)
This article focuses on social capital, a means for women working in the putting-out system sector to rise from adversity during the Covid-19 pandemic. This study explains that the pandemic has had a significant impact on the socioeconomic activities of women workers in Kalirungkut, Surabaya. This study aims to analyse working women who experience social downturns to get back up with the social capital they have. This qualitative research uses a non-positivistic paradigm but an interpretive approach through observation and in-depth interviews involving informants exposed to COVID-19. This study found four categories: helping behaviour as an act of humanitarian solidarity; reforestation and vegetable planting movement; networks for physical and social health services; and strengthening the economy. The researchers concluded that the social capital possessed by women workers in the putting-out system increased women's enthusiasm to rise from adversity during the Covid-19 pandemic.